A Low-Cost Wearable Remote Healthcare Monitoring System - Elango, Konguvel; Muniandi, Kannan (Role of Edge Analytics in Sustainable Smart City Development, 2020)
One main area of research that has seen adoption of the technology is the healthcare sector. With the advancements in technology and miniaturization of sensor nodes, there have been many attempts to utilize the new technology in various areas to improve the quality of human life. This chapter is an attempt to solve a healthcare problem that the society faces. The main objective is to design and develop a wearable healthcare monitoring system. This system includes detection of a fall of a human subject under consideration, detection of heart rate and detection of body temperature. Remote viewing of the sensed data enables a health care specialist to monitor a patient's health condition. This wearable health monitoring system can be made with easily available sensors with an interpretation of making the system inexpensive.